2016
DOI: 10.1016/j.molcel.2016.05.034
|View full text |Cite
|
Sign up to set email alerts
|

Release of SR Proteins from CLK1 by SRPK1: A Symbiotic Kinase System for Phosphorylation Control of Pre-mRNA Splicing

Abstract: Summary Phosphorylation has been generally thought to activate the SR family of splicing factors for efficient splice-site recognition, but this idea is incompatible with an early observation that overexpression of an SR protein kinase, such as the CDC2-like kinase 1 (CLK1), weakens splice-site selection. Here we report that CLK1 binds SR proteins, but lacks the mechanism to release phosphorylated SR proteins, thus functionally inactivating the splicing factors. Interestingly, CLK1 overcomes this dilemma throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
104
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 85 publications
(115 citation statements)
references
References 42 publications
6
104
0
4
Order By: Relevance
“…In control experiments we demonstrated that, unlike SRPK1, CLK1 stays attached to GST-RS2 after phosphorylation (compare lanes 1–3 in Fig. 2B) in keeping with prior reports showing that CLK1 binds with high affinity to both the phosphorylated and unphosphorylated RS domain of SRSF1 26, 41 . Overall, these findings indicate that CLK1 phosphorylation of RS2 breaks contacts with RRM1, promoting PP1 binding to the SR protein.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…In control experiments we demonstrated that, unlike SRPK1, CLK1 stays attached to GST-RS2 after phosphorylation (compare lanes 1–3 in Fig. 2B) in keeping with prior reports showing that CLK1 binds with high affinity to both the phosphorylated and unphosphorylated RS domain of SRSF1 26, 41 . Overall, these findings indicate that CLK1 phosphorylation of RS2 breaks contacts with RRM1, promoting PP1 binding to the SR protein.…”
Section: Resultssupporting
confidence: 91%
“…However, either SRPK1 or CLK1 expression can diffuse speckles suggesting that hyper-phosphorylation may serve a general role in mobilizing SR proteins for splicing activities 19,20,2325 . We showed recently that SRPK1 and CLK1 form a nuclear complex that activates splicing function and plays a synergistic role in controlling RS domain phosphorylation and SR protein release from CLK1 26 . Both SRPKs and CLKs are often over-expressed in various cancers emphasizing the relationship between SR protein phosphorylation and splicing as well as the potential for therapeutic intervention through kinase inhibition strategies 27,28 .…”
Section: Introductionmentioning
confidence: 99%
“…New light has been shed on this by two recent studies that show that SRPK1, after being localized to the nucleus, facilitates the dissociation of SRSF1 from the nuclear speckles by the formation of an SRPK1-CLK1 complex. The presence of SRPK1 facilitates the release of SRSF1 from CLK1 and enhances further phosphorylation of SP dipeptides, resulting in the mobilization of SRSF1 from nuclear speckles to nucleoplasm (50,51). In this study, we observed that SRPK2 also plays a role in the mobilization of SRSF3 from the speckles to nucleoplasm.…”
Section: Phosphorylation Mechanisms Of Sr Proteinssupporting
confidence: 55%
“…In cells, most SRPK1 is localized in the cytoplasm where it catalyzes SR protein phosphorylation to facilitate their nuclear transport (Kataoka et al, 1999; Lai et al, 2001; Zhong et al, 2009), and this process is accelerated in response to extracellular stimuli (Nowak et al, 2010). Once in the nucleus, SRPK1 can synergize with additional SR protein kinases, such as the CLK family of kinases predominantly localized in the nucleus, to further phosphorylate SR proteins to promote spliceosome assembly (Aubol et al, 2016). During splicing, SR proteins become dephosphorylated by nuclear phosphatases, and like most phosphorylation-regulated proteins, SR proteins are regulated via this phosphorylation-dephosphorylation cycle in different cellular compartments (Misteli et al, 1998; Ngo et al, 2005; Huang and Steitz, 2001; Huang et al, 2003; Sanford et al, 2004).…”
Section: Introductionmentioning
confidence: 99%